2016
DOI: 10.1002/psc.2926
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation with peptide assemblies carrying Lewis y tumor‐associated carbohydrate antigen

Abstract: Molecular assemblies varying morphologies in a wide range from spherical micelle, nanosheet, curved sheet, nanotube and vesicle were prepared and loaded with Lewis y (Le ) tumor-associated carbohydrate antigen on the assembly surface. The molecular assemblies were composed of poly(sarcosine) -block-poly(L-lactic acid) (m = 15 or 50, Lactosome), poly(sarcosine) -block-(D/L-Leu-Aib) (m = 22 or 30, n = 6 or 8) and their combinations. The molecular assemblies carrying Le on the surface were administered in BALB/c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In addition, Yamazaki and co-workers also investigated immune activation with polypeptide assemblies carrying Lewis y (Figure ). Carbohydrate antigen Lewis y was conjugated to poly­(sarcosine) n - b -poly­( l -lactic acid) 30 ( m = 15 or 50) and poly­(sarcosine) m - b -( d / l -Leu-Aib) n ( m = 22 or 30, n = 6 or 8). It was shown that the presentation and the antigenicity of Lewis y are largely dependent on the morphologies of the molecular assemblies.…”
Section: Immunologymentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, Yamazaki and co-workers also investigated immune activation with polypeptide assemblies carrying Lewis y (Figure ). Carbohydrate antigen Lewis y was conjugated to poly­(sarcosine) n - b -poly­( l -lactic acid) 30 ( m = 15 or 50) and poly­(sarcosine) m - b -( d / l -Leu-Aib) n ( m = 22 or 30, n = 6 or 8). It was shown that the presentation and the antigenicity of Lewis y are largely dependent on the morphologies of the molecular assemblies.…”
Section: Immunologymentioning
confidence: 95%
“…In addition, Yamazaki and co-workers also investigated immune activation with polypeptide assemblies carrying Lewis y (Figure 72). 572 It was shown that the presentation and the antigenicity of Lewis y are largely dependent on the morphologies of the molecular assemblies. Among the various morphologies, including nanosheet, curved sheet, nanotube, and vesicle, a nanosheet possessing the highest density of Lewis y displayed the best effect to produce anti-Lewis y IgM.…”
Section: Carbohydrate-based Vaccine and Immunotherapymentioning
confidence: 99%
“…[30] On the contrary, nanoparticles were used as a vehicle for a tumor-associated carbohydrate antigen (TACA) to trigger the immune response. [31] In this case, nanoparticles displayed TACA as well as poly(sarcosine) on the surface, but antigenicity of poly(sarcosine) could be lowered apparently by making the surface density of poly(sarcosine) as high as polymer brush. As a result, TACA becomes the main component on the surface left behind as an antigen to promote the antibody production.…”
Section: Introductionmentioning
confidence: 90%
“…A biological design was also examined to use sialic acid, which will induce B cell apoptosis upon binding to Siglec‐G and CD22 which are expressed on mouse B cell. On the contrary, nanoparticles were used as a vehicle for a tumor‐associated carbohydrate antigen (TACA) to trigger the immune response . In this case, nanoparticles displayed TACA as well as poly(sarcosine) on the surface, but antigenicity of poly(sarcosine) could be lowered apparently by making the surface density of poly(sarcosine) as high as polymer brush.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness was about 10 nm, indicating the interdigitated monolayer structure comprising the heterochiral helical peptides. The surface density of poly­(sarcosine) on the nanosheet was so high that immune cells could not recognize a possible antigen of poly­(sarcosine) chains covering the nanosheet. , Furthermore, the surfaces of molecular assemblies prepared from SL and SD were able to be functionalized with thiol, , adenine, and oligosaccharide , by their introductions at the terminal of poly­(sarcosine) chains. Accordingly, the peptide nanosheets can be designed to have two faces, one for the phenylboronic acid to connect to antibodies and the other for the photoactivatable radical generator to react with PP fiber.…”
Section: Introductionmentioning
confidence: 99%